Medieneffekte und -reflexionen im Erstdruck von Theodor Fontanes "Stechlin" in "Über Land und Meer" - Gretz, Daniela (Fontanes Medien)

Ein Blick auf: Verstetigung und Transfer im Bundesprogramm „Kita-Einstieg: Brücken bauen in frühe Bildung“ - Albers, Timm; Hoeft, Maike; Abendroth, Sonja; Meusel, Sarah

Erkenntnisse zu Verstetigung und Transfer im Bundesprogramm "Kita-Einstieg: Brücken bauen in frühe Bildung" - Abendroth, Sonja; Hoeft, Maike; Meusel, Sarah

'Surprised, Shocked, Worried': User Reactions to Facebook Data Collection from Third Parties - Arias Cabarcos, Patricia; Khalili, Saina; Strufe, Thorsten (arXiv:2209.08048)
Data collection and aggregation by online services happens to an extent that is often beyond awareness and comprehension of its users. Transparency tools become crucial to inform people, though it is unclear how well they work. To investigate this matter, we conducted a user study focusing on Facebook, which has recently released the "Off-Facebook Activity" transparency dashboard that informs about personal data collection from third parties. We exposed a group of n = 100 participants to the dashboard and surveyed their level of awareness and reactions to understand how transparency impacts users' privacy attitudes and intended behavior. Our participants were surprised about the massive amount of collected data, became significantly less comfortable with data collection, and more likely to take protective measures. Collaterally, we observed that current consent schemes are inadequate. Based on the survey findings, we make recommendations for more usable transparency and highlight the need to raise awareness about transparency tools and to provide easily actionable privacy controls.

(Semi-)Automatische Kommentarmoderation zur Erhaltung Konstruktiver Diskurse - Niemann, Marco; Assenmacher, Dennis; Brunk, Jens; Riehle, Dennis Maximilian; Becker, Jörg; Trautmann, Heike (Hate Speech — Definitionen, Ausprägungen, Lösungen)

Textual One-Pass Stream Clustering with Automated Distance Threshold Adaption - Assenmacher, D; Trautmann, Heike (Intelligent Information and Database Systems)

Benchmarking Crisis in Social Media Analytics: A Solution for the Data-Sharing Problem - Assenmacher, Dennis; Weber, Derek; Preuss, Mike; Valdez, André Calero; Bradshaw, Alison; Ross, Björn; Cresci, Stefano; Trautmann, Heike; Neumann, Frank; Grimme, Christian (Social Science Computer Review)
Computational social science uses computational and statistical methods in order to evaluate social interaction. The public availability of data sets is thus a necessary precondition for reliable and replicable research. These data allow researchers to benchmark the computational methods they develop, test the generalizability of their findings, and build confidence in their results. When social media data are concerned, data sharing is often restricted for legal or privacy reasons, which makes the comparison of methods and the replicability of research results infeasible. Social media analytics research, consequently, faces an integrity crisis. How is it possible to create trust in computational or statistical analyses, when they cannot be validated by third parties? In this work, we explore this well-known, yet little discussed, problem for social media analytics. We investigate how this problem can be solved by looking at related computational research areas. Moreover, we propose and implement a prototype to address the problem in the form of a new evaluation framework that enables the comparison of algorithms without the need to exchange data directly, while maintaining flexibility for the algorithm design.

Auf Deutsch gesagt: eine Wortschatzkunde für Deutsch als Fremdsprache - Kilsbach, Sebastian; Augst, Gerhard

EFFECT OF SHREDDING PARAMETERS ON THE FORMATION OF AIRBORNE FIBER DUST DURING MECHANICAL RECYCLING OF FIBER-REINFORCED THERMOPLASTICS - Hopp, Matthias; Tölle, Lisa (Proceedings of the 20th European Conference on Composite Materials)

Zero-Sequence Voltage Reduces DC-Link Capacitor Demand in Cascaded H-Bridge Converters for Large-Scale Electrolyzers by 40% - Unruh, Roland; Schafmeister, Frank; Böcker, Joachim (24th European Conference on Power Electronics and Applications (EPE'22 ECCE Europe))
Cascaded H-bridge Converters (CHBs) are a promising solution in converting power from a three-phase medium voltage of 6.6 kV...30 kV to a lower DC-voltage in the range of 100 V...1 kV to provide pure DC power to applications such as electrolyzers for hydrogen generation, data centers with a DC power distribution and DC microgrids. CHBs can be interpreted as modular multilevel converters with an isolated DC-DC output stage per module, require a large DC-link capacitor for each module to handle the second harmonic voltage ripple caused by the fluctuating input power within a fundamental grid period. Without a zero-sequence voltage injection, star-connected CHBs are operated with approximately sinusoidal arm voltages and currents. The floating star point potential enables to utilize different zero-sequence voltage injection techniques such as a third-harmonic injection with 1/6 of the grid voltage amplitude or a Min-Max voltage injection. Both well-known methods have the advantage to reduce the peak arm voltage and thereby the number of required modules by 13.4 % (to √ 3 2). This paper proves analytically that the third-harmonic injection with 1/6 of the grid voltage amplitude reduces the second harmonic voltage ripple by only 15.1 % compared to no-voltage injection for unity power factor operation and balanced grid voltages. Then it is shown, that the Min-Max injection has the often overlooked advantage of reducing the second harmonic voltage ripple by even 18.8 %. By applying the here proposed zero-sequence voltage injection in saturation modulation, the second harmonic voltage ripple of the DC-link capacitors is reduced by even 24.3 %, while still requiring the same number of modules as the Min-Max injection. For a realistic number of reserve modules, the overall energy ripple in the DC-link capacitors is reduced by 40 %.
Keywords: Cascaded H-Bridge; Solid-State Transformer; Zero sequence voltage; Third harmonic injection; Capacitor voltage ripple

Neural Network Based Carrier Frequency Offset Estimation From Speech Transmitted Over High Frequency Channels - Heitkämper, Jens; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (Proceedings of the 30th European Signal Processing Conference (EUSIPCO))
The intelligibility of demodulated audio signals from analog high frequency transmissions, e.g., using single-sideband (SSB) modulation, can be severely degraded by channel distortions and/or a mismatch between modulation and demodulation carrier frequency. In this work a neural network (NN)-based approach for carrier frequency offset (CFO) estimation from demodulated SSB signals is proposed, whereby a task specific architecture is presented. Additionally, a simulation framework for SSB signals is introduced and utilized for training the NNs. The CFO estimator is combined with a speech enhancement network to investigate its influence on the enhancement performance. The NN-based system is compared to a recently proposed pitch tracking based approach on publicly available data from real high frequency transmissions. Experiments show that the NN exhibits good CFO estimation properties and results in significant improvements in speech intelligibility, especially when combined with a noise reduction network.

Data-driven Time Synchronization in Wireless Multimedia Networks - Afifi, Haitham; Karl, Holger; Gburrek, Tobias; Schmalenstroeer, Joerg (2022 International Wireless Communications and Mobile Computing (IWCMC))

Voluntary Submission and the ʻPolitics of Truth’: Nietzsche and Foucault on the Danger of the Fully Normalised ‘Last Human’ - Corall, Niklas (Nietzsche and the Politics of Difference)

Warum Personalführung in Start-ups anders funktioniert - Hubner-Benz, Sylvia

Creating social and environmental value through integrated thinking: International evidence - Reimsbach, Daniel; Braam, Geert (Business Strategy and the Environment)
Abstract Integrated thinking (IT) is a managerial mindset increasingly discussed in the context of value creation. Through the lens of systems theory, this study examines how the degree to which IT is embedded in a firm's strategy and day‐to‐day business processes is associated with the firm's social and environmental value creation. Using a broad international dataset, we find strong evidence that our measure of IT is positively related to a firm's sustainability performance (SP), which we use to operationalize social and environmental value creation (or erosion). Our results also reveal that the increase in a firm's SP might come at the cost of a short‐term decrease in financial performance (FP). We find no indication, however, that IT induces a trade‐off between SP and long‐term FP. Integrated thinking appears to stipulate long‐term financial value creation instead. We further explore moderating factors within the organizational and institutional context of our sample firms and highlight implications for society, corporate practice, and policymaking.
Keywords: Management; Monitoring; Policy and Law; Strategy and Management; Geography; Planning and Development; Business and International Management

New aspects of modeling and operation of nitrous gas absorption in packed columns - Mackowiak, Jan F.; Franke, Patrick; Chromik, Reiner; Mackowiak, Jerzy (Proceedings of the 12th International Conference Distillation & Absorption Toulouse)

Eye-Tracking Studie zu Textaufgaben in Klasse 5: Bemerken und Interpretieren syntaktischer Strukturen - Dröse, Jennifer; Neugebauer, P.; Delucchi Danhier, R.; Mertins, B. (Eye-Tracking in der Mathematik- und Naturwissenschaftsdidaktik. Forschung und Praxis)

Procrastination Among University Students: Differentiating Severe Cases in Need of Support From Less Severe Cases - Rozental, Alexander; Forsström, David; Hussoon, Ayah; Klingsieck, Katrin B. (Frontiers in Psychology)
Procrastination refers to voluntarily postponing an intended course of action despite expecting to be worse off for this delay, and students are considered to be especially negatively affected. According to estimates in the literature, at least half of the students believe procrastination impacts their academic achievements and well-being. As of yet, evidence-based ideas on how to differentiate severe from less severe cases of procrastination in this population do not exist, but are important in order to identify those students in need of support. The current study recruited participants from different universities in Sweden to participate in an anonymous online survey investigating self-rated levels of procrastination, impulsivity, perfectionism, anxiety, depression, stress, and quality of life. Furthermore, diagnostic criteria for pathological delay (PDC) as well as self-report items and open-ended questions were used to determine the severity of their procrastination and its associated physical and psychological issues. In total, 732 participants completed the survey. A median-split on the Pure Procrastination Scale (PPS) and the responses to the PDC were used to differentiate two groups; “less severe procrastination” (PPS ≤ 2.99; n = 344; 67.7% female; M age = 30.03; SD age = 9.35), and “severe procrastination” (PPS ≥ 3.00; n = 388; 66.2% female; M age = 27.76; SD age = 7.08). For participants in the severe group, 96–97% considered procrastination to a problem, compared to 42–48% in the less severe group. The two groups also differed with regard to considering seeking help for procrastination, 35–38% compared to 5–7%. Participants in the severe group also reported more problems of procrastination in different life domains, greater symptoms of psychological issues, and lower quality of life. A thematic analysis of the responses on what physical issues were related to procrastination revealed that these were characterized by stress and anxiety, e.g., tension, pain, and sleep and rest, while the psychological issues were related to stress and anxiety, but also depression, e.g., self-criticism, remorse, and self-esteem. The current study recommends the PPS to be used as an initial screening tool, while the PDC can more accurately determine the severity level of procrastination for a specific individual.
Keywords: General Psychology

Delaying Academic Tasks and Feeling Bad About It - Bobe, Julia; Schnettler, Theresa; Scheunemann, Anne; Fries, Stefan; Bäulke, Lisa; Thies, Daniel O.; Dresel, Markus; Leutner, Detlev; Wirth, Joachim; Klingsieck, Katrin B.; Grunschel, Carola (European Journal of Psychological Assessment)
Abstract. Procrastination is the irrational delay of an intended task and is common among students. A delay can only be defined as procrastination when it is voluntary, the action was intended but not implemented, and the delay is accompanied by subjective discomfort. Established scales of procrastination cover mainly behavioral aspects but have neglected the emotional aspect. This inaccuracy concerning the construct validity might entail misconceptions of procrastination. Accordingly, we developed and validated the Behavioral and Emotional Academic Procrastination Scale (BEPS), which covers all aspects of the definition of procrastination. The 6-item scale measuring self-reported academic procrastination was tested in three studies. Study 1 ( N = 239) evaluated the psychometric qualities of the BEPS, indicating good item characteristics and internal consistency. Study 2 ( N = 1,441) used confirmatory factor analysis and revealed two correlated factors: one covering the behavioral aspect and the other reflecting the emotional aspect. Measurement invariance was shown through longitudinal and multigroup confirmatory factor analyses. Study 3 ( N = 234) provided evidence for the scale’s convergent validity through correlations with established procrastination scales, self-efficacy, and neuroticism. The BEPS thus economically operationalizes all characteristics of academic procrastination and appears to be a reliable and valid self-report measure.
Keywords: Applied Psychology

Wie können unterschiedliche Aspekte diagnostischer Kompetenz gefördert werden? - Grotegut, Lea; Klingsieck, Katrin B. (Zeitschrift für Pädagogische Psychologie)
Zusammenfassung. Eine gut ausgebildete diagnostische Kompetenz von Lehrpersonen ist eine wesentliche Voraussetzung für gelingenden Unterricht und trägt maßgeblich zur akademischen und persönlichen Entwicklung von Schülern bei. Häufig sind Lehrpersonen jedoch nur bedingt dazu in der Lage, Schülermerkmale wie Leistung, Motivation oder Ängstlichkeit adäquat zu beurteilen. Eine Förderung der diagnostischen Kompetenz sollte bereits während des Studiums stattfinden, um Lehrpersonen früh auf diagnostische Situationen in der Schulpraxis vorzubereiten und negative Konsequenzen möglicher pädagogischer Fehlentscheidungen zu vermeiden. Dieser Beitrag vergleicht eine lehrendenzentrierte, eine problembasierte und eine digitale, simulationsbasierte Maßnahme zur Förderung unterschiedlicher Aspekte diagnostischer Kompetenz an einer Stichprobe von N = 166 Lehramtsstudierenden im Hinblick auf ihre Wirksamkeit. Es zeigen sich insbesondere Vorteile der simulationsbasierten Fördermaßnahme in den Bereichen intrinsische Motivation und Interesse sowie Nachteile der lehrendenzentrierten Maßnahme im Bereich des Wissens um das systematische Vorgehen im diagnostischen Prozess und der problembasierten Maßnahme im Bereich des Extraneous Cognitive Load. Die Ergebnisse werden insbesondere im Hinblick auf ihre praktischen Implikationen im Rahmen der Lehrerbildung und zunehmend digitalisierter Lehre diskutiert.
Keywords: Developmental and Educational Psychology